Highest Diploid Number Among Gymnotiformes: First Cytogenetic Insights into Rhabdolichops (Sternopygidae) - Suarez, Pablo; Guerreiro Pinto Barroso, Inae Cristina; Silva, Danillo dos Santos; Milhomem, Susana S. R.; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Martins, Cesar [UNESP]; Pieczarka, Julio Cesar; Nagamachi, Cleusa Yoshiko (Mary Ann Liebert, Inc, 2017)
We report the first comparative cytogenetic analysis of two species from electrogenic fish of genus Rhabdo-lichops (Sternopygidae, Gymnotiformes): Rhabdolichops troscheli and Rhabdolichops cf eastwardi. R. troscheli has 2n = 54 (fundamental number [FN] = 66), whereas R. cf. eastwardi has 2n = 74 (FN = 78). C-banding revealed centromeric constitutive heterochromatin in both species. Ag-NORs mapped on pair 6 in R. troscheli and pair 30 in R. cf eastwardi. Fluorescense in situ hybridization with 18S rDNA probes confirmed the Ag-NOR staining results and revealed additional (presumably silent) ribosomal genes on pairs 12, 13, 21, 23, 26, and 27 in R. cf eastwardi. 5S rDNA was found on the centromeres of pair 7 in both species. Telomeric probes showed only distal locations. Dispersed signal patterns were obtained using probes for retrotransposons Rex1 and Rex3. Histone H1 and H3 genes were found together on pair 6 in R. cf eastwardi. The high diploid number found in Rhabdolichops suggests that chromosome fission may have contributed to its chromosomal evolution, phylogenetic relationship of the Sternopygidae suggests that this increase in diploid number could be a synapomorphic characteristic of genus Rhabdolichops. Although both species are phylogenetically close related, their karyotype structure has undergone divergent evolutionary directions. All in all, our results strongly suggest that R. cf eastwardi experencied recent intense genome reorganization.
Keywords: electric fish; chromosomes; biodiversity; Amazon rainforest; karyotypic diversity